HUBUNGAN DUKUNGAN SUAMI TERHADAP KEJADIAN POSTPARTUM BLUES PADA IBU PRIMIPARA DI WILAYAH KERJA PUSKESMAS SIGOMPUL KECAMATAN LINTONG NIHUTA KABUPATEN HUMBANG HASUNDUTAN - Esther Siringo-ringo (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Postpartum blues or often called baby blues or maternity blues is a mild psychological disorder that occurs temporarily, namely 2 days to 2 weeks after giving birth, which is characterized by anxiety, easy panic, fatigue, often blaming yourself and feeling unable to take care of the baby. This research aims to determine the relationship between husband's support, family support and adjustment to the new role as a mother with the incidence of postpartum blues in the working area of ​​the Sigompul Community Health Center, Lintong Nihuta District, Humbang Hsundutan Regency in 2023. Quantitative research with a cross-sectional design, was conducted in the working area of ​​the Community Health Center Sigompul Kec. Lintong Nihuta Kab. Humbang Hasundutan from January to May 2023. The respondents for this research were 80 people. Sampling was carried out using proportional sampling technique. The research instrument used was a questionnaire. Univariate and bivariate analysis used chi square (p<0.05).